Aktivitas Antibakteri Kombinasi Ekstrak Etanol Kulit Kopi Robusta dan Serai Wangi terhadap Escherichia coli - Ibrahim Ayattulah; Suci Rahmawati; Dwi Kurnia Putri; Tri Danang Kurniawan; Rose Intan Perma Sari (Yayasan Literasi Sains Indonesia, 2026)
Antibacterial activity of a combination of 70% ethanol extracts of Robusta coffee peel (Coffea canephora) and citronella grass (Cymbopogon nardus) against Escherichia coli was evaluated using the disc diffusion (Kirby–Bauer) method. The extracts were obtained through maceration with 70% ethanol and combined in a 1:1 ratio at concentrations of 10%, 20%, 40%, 60%, and 80%. The parameter observed was the diameter of the inhibition zone formed around the discs. The results showed no antibacterial activity at concentrations of 10% and 20%. At 40%, the inhibition zone was 4.87 mm (weak category), increasing to 5.43 mm (moderate category) at 60% and 7.53 mm (moderate category) at 80%. The positive control (ciprofloxacin) exhibited an inhibition zone of 23.31 mm (very strong category), while the negative control (DMSO) showed no inhibition. Statistical analysis using One Way ANOVA indicated significant differences among treatments (p<0.05). In conclusion, the combination of 70% ethanol extracts of Robusta coffee peel and citronella grass demonstrated concentration-dependent antibacterial activity against Escherichia coli, although the activity remained in the weak to moderate category.